Empirical research on user satisfaction with the transport and the supporting services at Croatian airports - Naletina, Dora (Array, 2019)
Air traffic is a very important traffic branch, since it provides the possibility of fast travelling long distances between countries and contributes to the development of economy, trade and tourism. The number of long-distance travels has been increasing, people have started to travel more and therein, the importance of air traffic has been growing. The Republic of Croatia has to take advantage of its favourable geographical position at the crossroads of West and East Europe, which facilitates the development of air traffic. Airports have major significance for the development of air traffic, and it is of great importance that they provide high quality services, i.e. that their users are satisfied. With the aim of establishing the level of user satisfaction with transportation and the supporting services in Croatian airports, an empirical research via an online survey has been conducted, where the respondents were asked about how often they used the airports in the Republic of Croatia, their supporting services, the importance of the factors influencing the decision-making on buying the ticket for the specific airline and overall satisfaction with the services in Croatian airports. The results of the primary research suggest that the users, when deciding on buying the ticket, put the price and safety first. The users are not entirely satisfied with the price-quality ratio and are not content with the prices of the parking in airports and with the airport facilities that provide hospitality services. Furthermore, it has been established that user satisfaction with transportation and the supporting services can be perceived through three factors: 1) additional services; 2) user satisfaction with additional services; 3) satisfaction with the staff and prices of additional services. The paper also analysed user satisfaction with transportation and the supporting services considering socio-demographic characteristics of the respondents.